The Impact of Pre-Trial Detention on Prison Overcrowding: Perspectives From Indonesia's Criminal Justice System - Hamja Hamja (Jurnal Wawasan Yuridika, 2024)
The decision to detain suspects in detention centers or prisons has contributed to the rising occupancy rates, leading to overcrowding in prisons. This study aims to understand the fundamental values underpinning the implementation of pre-trial detention policies in Indonesia and their impact on the increased congestion in prison facilities. The study employs a descriptive approach with a normative juridical research type. The issues are examined using statutory and conceptual approaches. Data collection is conducted through a literature review, and the data is analyzed qualitatively. The research findings reveal that the law provides a robust foundation for implementing alternative offender penalties aside from imprisonment. However, the understanding of law enforcement officers as instruments of law enforcement still tends to favour decisions on pre-trial detention and large-scale detentions. Social and political factors remain the primary basis for the application of suspect detention, subsequently driving the escalation of prison overcrowding cases.